Política Nacional de Saúde Mental: a contrarreforma neoliberal - Oliveira, Paloma Azevêdo de (2022)
In recent years, we have seen the Brazilian mental health policy been submiitted through several changes that, somehow, reissued the hospital-centered model whose history reveals a privatist character of the health system. What was once idealized as a policy that aimed to continue a process of dehospitalization in the field of mental health, within the scope of a broad Psychiatric Reform, begin to worry users and professionals of the psychosocial care network by presenting obsolete and aggressive methods that resemble asylum treatment. The purpose of this research is to understand the dynamics of the neoliberal counter-reform in the national mental health policy, seeking to understand its main components, which were implemented throughout the 1990s and 2010s, as well as those introduced after the 2016 Coup and in the first years of the right-wing government of Jair Bolsonaro. Therefore, this study prioritized a bibliographic and documentary research, in order to identify and analyze the traits of the counter-reform since the implementation of the mental health policy, analyzing, in particular, the main laws and rules that regulate the field of mental health, as well as the criticism in the scientific debate around the affirmation of neoliberal hegemony. We conclude by highlighting the process of increasingly intense participation of the private sector in directing public resources, contrary to the objectives and principles of the SUS and also the Brazilian Psychiatric Reform